SERUM proBRAIN NATRIURETIC PEPTIDE IN MIGRAINE PATIENTS - Abbasi, Sana Qanber (Pakistan Journal of Physiology, 2016)
Background: Migraine is one of the commonest of primary headache syndromes rated by WHO to be as disabling as a day with quadriplegia, psychosis and dementia. Migraine has been found to be associated with increased levels of pro BNP that may indicate preclinical cardiac involvement in patients with migraine. Objectives were to compare the levels of serum proBNP among migraineurs and healthy controls and to find out whether proBNP measurement could represent as a potential biomarker of identifying asymptomatic migraineurs. Methods: This was a cross sectional comparative study in which serum proBNP levels were measured and compared between 35 migraine patients (24 females and 11 males) and 16 healthy controls (13 males and 3 females). Results: Serum proBNP levels were raised in migraine group than the healthy controls and the results were significant (p=0.00). Serum proBNP levels were 32.0±11.5 ηg/L in migraine group and 21.63±8.7 ηg/L in healthy controls. Conclusion: Raised serum proBNP levels indicate that the patient is prone to develop migraine. Pak J Physiol 2016;12(4):21–3